Modified titanium dioxide nanotube and preparation method thereof, water electrolysis catalytic electrode and preparation method thereof, and water electrolysis hydrogen production device

Through the preparation method of modified titanium dioxide nanotubes, the problem of low conductivity of titanium-based oxide catalytic electrodes is solved, and the catalytic electrodes is achieved is achieved with high conductivity, stability and low cost, and the efficiency and economicality of electrolyzed hydrogen production are improved.

CN119683678APending Publication Date: 2025-03-25HUANENG YIMIN COAL POWER CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411812698.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The titanium-based oxide catalytic electrode used for hydrogen production in the prior art has low conductivity, resulting in stability and cost problems under high current density and extreme electrochemical environments.

Method used

The preparation method of modified titanium dioxide nanotubes includes mixing titanium dioxide nanoparticles with alkali solution, heating reaction, washing and high-temperature annealing, and then undergoing modification and annealing with aluminum powder in an inert gas to improve its catalytic activity and electrical conductivity.

Benefits of technology

It significantly improves the conductivity, chemical stability and corrosion resistance of the catalytic electrode, extends the life of the catalyst, and reduces the overall cost of hydrogen production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683678A_ABST
    Figure CN119683678A_ABST
Patent Text Reader

Abstract

The invention provides a modified titanium dioxide nanotube and a preparation method thereof, a water electrolysis catalytic electrode and a preparation method thereof, and a water electrolysis hydrogen production device. The preparation method of the modified titanium dioxide nanotube comprises the following steps: S1, mixing titanium dioxide nanoparticles with a first alkali solution to obtain a titanium dioxide nanoparticle dispersion liquid, heating the titanium dioxide nanoparticle dispersion liquid for reaction, washing a reaction product with acid, ethanol and water, and performing high-temperature annealing to obtain a TiO2 nanotube; and S2, aluminum powder and the TiO2 nanotube are placed on the upstream and downstream of gas of a tubular furnace correspondingly, modified annealing treatment is conducted, and the modified titanium dioxide nanotube is obtained. The catalytic activity of the titanium dioxide nanotube is obviously improved, the conductivity of the titanium dioxide nanotube is obviously improved while the stability of the material is guaranteed, the titanium dioxide nanotube is applied to a catalytic electrode, the electrode can have good chemical stability, corrosion resistance and conductivity, and the overall performance of the catalytic electrode is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen production by electrolysis of water, and in particular to a modified titanium dioxide nanotube and a preparation method thereof, a water electrolysis catalytic electrode and a preparation method thereof, and a water electrolysis hydrogen production device. Background Art

[0002] In recent years, the world has started to adjust its energy structure and shift its energy resource development. Clean energy deployment has become a hot topic and an urgent task. Hydrogen energy, as a high-energy-density, pollution-free, zero-carbon clean energy, is regarded as an ideal alternative energy source and is receiving widespread attention and development. As a green hydrogen production technology, water electrolysis has attracted widespread attention due to its environmental friendliness and renewability, and has huge market potential.

[0003] However, in the process of developing dynamic, efficient, stable and low-cost hydrogen production, proton exchange membrane (PEM) water electrolysis technology and anion exchange membrane (AEM) water electrolysis technology are facing development bottlenecks, and key materials such as catalytic electrodes and diaphragms need to be broken through. As far as catalytic electrodes are concerned, the main challenges currently faced include high-cost precious metal catalysts and the stability of catalytic electrodes, especially the operating state under high current density. In actual production, catalytic electrodes need to withstand extreme electrochemical environments such as high current density and acid-base environment. Catalytic electrodes are required to have good chemical stability and structural stability, reduce the frequency of catalyst replacement, reduce overall costs, and improve the economy of water electrolysis systems.

[0004] Titanium-based materials are ideal materials for preparing catalytic electrodes for water electrolysis due to their excellent chemical stability and corrosion resistance. They are often used as diffusion layer substrates or composite catalyst substrates to improve the stability of the system. However, the inherent electrical conductivity of titanium-based oxides is insufficient, which affects the performance of composite electrodes to a certain extent. Summary of the invention

[0005] The main purpose of the present invention is to provide a modified titanium dioxide nanotube and a preparation method thereof, a water electrolysis catalytic electrode and a preparation method thereof, and a water electrolysis hydrogen production device, so as to solve the problem of low conductivity of titanium-based oxides used for hydrogen production in the prior art in catalytic electrodes.

[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a method for preparing modified titanium dioxide nanotubes is provided, and the preparation method comprises: step S1, mixing titanium dioxide nanoparticles and a first alkaline solution to obtain a titanium dioxide nanoparticle dispersion, heating the titanium dioxide nanoparticle dispersion for reaction, washing the reaction product with acid, ethanol and water, and then annealing at high temperature to obtain TiO2 nanotubes; step S2, placing aluminum powder and TiO2 nanotubes in the gas upstream and downstream of a tubular furnace respectively, and performing modification annealing treatment to obtain modified titanium dioxide nanotubes.

[0007] Further, the temperature of the modified annealing treatment is 500-700°C, preferably 550-600°C;

[0008] The time of modified annealing treatment is 2-8h, preferably 4-6h;

[0009] The heating rate of the modified annealing treatment is 2-30°C / min, preferably 5-15°C / min;

[0010] The cooling rate of the modified annealing treatment is 2-30°C / min, preferably 5-20°C / min;

[0011] The mass ratio of aluminum powder to TiO2 nanotubes is 3-15:1, preferably 5-10:1;

[0012] The modification annealing is performed in an inert gas atmosphere, wherein the inert gas includes any one or more of nitrogen, argon and helium.

[0013] Further, the concentration of the first alkali solution is 3-18 mol / L, and the first alkali solution is an aqueous solution of any one or more of potassium hydroxide and sodium hydroxide;

[0014] The dispersion concentration of titanium dioxide nanoparticles in the titanium dioxide nanoparticle dispersion is 5-20 mg / mL;

[0015] The reaction temperature in step S1 is 100-210°C and the reaction time is 24-96h;

[0016] The temperature of the high temperature annealing treatment in step S1 is 350-750°C, preferably 400-600°C;

[0017] The high temperature annealing treatment time in step S1 is 1-4h;

[0018] The heating rate and / or cooling rate of the high temperature annealing treatment in step S1 is 5-20° C. / min.

[0019] According to another aspect of the present application, a modified titanium dioxide nanotube is provided, which is prepared by any of the above-mentioned methods for preparing modified titanium dioxide nanotubes.

[0020] According to another aspect of the present application, a method for preparing a catalytic electrode for electrolyzing water is provided, and the preparation method comprises: step A1, coating a modified TNTs dispersion containing the above-mentioned modified titanium dioxide nanotubes on a diffusion layer substrate to obtain a TNTs diffusion layer; step A2, setting a multi-component non-precious metal layer on the surface of the TNTs diffusion layer to obtain a catalytic electrode precursor; the material of the multi-component non-precious metal layer comprises metal nickel, metal aluminum and metal M, and the metal M is selected from any one or more of cobalt, iron, molybdenum and copper; step A3, under stirring conditions, immersing the catalytic electrode precursor in a second alkaline solution, and then washing and drying to obtain a catalytic electrode for electrolyzing water.

[0021] Furthermore, the solvent of the modified TNTs dispersion is a water-alcohol mixed solution, preferably, the water-alcohol mixed solution includes ethylene glycol, lower alcohol and water; preferably, the volume fraction of ethylene glycol in the water-alcohol mixed solution is less than or equal to 8%, and the volume ratio of lower alcohol to water is 1-5:1; preferably, the lower alcohol includes any one or more of isopropanol, propanol, ethanol and methanol;

[0022] The modified TNTs dispersion includes an ionomer, and the mass ratio of the ionomer to the modified titanium dioxide nanotube is 0.5-0.2:1;

[0023] The concentration of modified titanium dioxide nanotubes in the modified TNTs dispersion is 10-35 mg / mL;

[0024] The diffusion layer substrate is any one or more of nickel felt, dense nickel foam, stainless steel felt, carbon paper and carbon cloth;

[0025] The loading amount of modified titanium dioxide nanotubes in the TNTs diffusion layer is 1-8 mg / cm 2 .

[0026] Further, the molar ratio of metal nickel to metal aluminum in the multi-element non-precious metal layer is 3-6:1, and the molar ratio of metal nickel to metal M is 1-5:1;

[0027] The method of setting the multi-element non-precious metal layer includes any one or more of vacuum evaporation, magnetron sputtering and plasma spraying;

[0028] The metal loading of the multi-element non-precious metal layer is 0.5-20 mg / cm 2 .

[0029] Further, the alkali in the second alkali solution includes any one or more of potassium hydroxide and sodium hydroxide, and the concentration of the second alkali solution is 0.01-0.5 mol / L;

[0030] In step A3, the stirring time is 0.5-10h, preferably 4h;

[0031] In step A3, the drying is vacuum drying, and the vacuum drying temperature is 60-90°C.

[0032] According to another aspect of the present application, a water electrolysis catalytic electrode is provided, which is prepared by any of the above-mentioned methods for preparing a water electrolysis catalytic electrode.

[0033] According to another aspect of the present application, a water electrolysis hydrogen production device is provided, wherein the water electrolysis device contains the above-mentioned water electrolysis catalytic electrode.

[0034] By applying the technical solution of the present invention, titanium dioxide nanotubes are prepared by a specific method, and the surface of the nanotubes is modified by aluminum powder, thereby improving the catalytic activity of the titanium dioxide nanotubes. While ensuring the stability of the material, its electrical conductivity is significantly improved. When applied to a catalytic electrode, the electrode can have good chemical stability, corrosion resistance and conductivity, and the overall performance of the catalytic electrode is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0036] Figure 1 A scanning electron microscope image of the surface of the catalytic electrode according to Example 1 of the present invention is shown;

[0037] Figure 2 A comparison chart of water electrolysis performance of the catalytic electrode according to Example 1 of the present invention and Comparative Example 1 is shown;

[0038] Figure 3 A comparison chart of the electrolytic water stability of the catalytic electrodes according to Example 1 of the present invention and Comparative Example 1 is shown. DETAILED DESCRIPTION

[0039] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0040] As analyzed in the background technology of this application, there is a problem in the prior art that titanium-based oxides used for hydrogen production have low conductivity in catalytic electrodes. In order to solve this problem, this application provides a modified titanium dioxide nanotube and a preparation method thereof, a water electrolysis catalytic electrode and a preparation method thereof, and a water electrolysis hydrogen production device.

[0041] According to a typical embodiment of the present application, a method for preparing modified titanium dioxide nanotubes is provided, which is characterized in that it includes: step S1, mixing titanium dioxide nanoparticles and a first alkaline solution to obtain a titanium dioxide nanoparticle dispersion, heating the titanium dioxide nanoparticle dispersion for reaction, washing the reaction product with acid, ethanol and water, and then annealing at high temperature to obtain TiO2 nanotubes (TNTs); step S2, placing aluminum powder and TiO2 nanotubes in the upstream and downstream of the gas of a tubular furnace, respectively, and performing a modification annealing treatment to obtain modified titanium dioxide nanotubes.

[0042] The present application adopts a specific method to prepare titanium dioxide nanotubes, and uses aluminum powder to modify the surface of the nanotubes, thereby improving the catalytic activity of the titanium dioxide nanotubes, significantly improving its electrical conductivity while ensuring the stability of the material. Applying it to a catalytic electrode can make the electrode have good chemical stability, corrosion resistance and electrical conductivity, significantly improving the overall performance of the catalytic electrode.

[0043] Titanium dioxide nanoparticles used as raw materials can be selected from the prior art, such as nano-grade titanium dioxide P25. Preferably, the average particle size of the titanium dioxide nanoparticles is 15-30 nm.

[0044] The type of the first alkali solution can be selected from the prior art. For example, the first alkali solution includes but is not limited to an aqueous solution of any one or more of potassium hydroxide and sodium hydroxide. In some embodiments of the present application, in order to further improve the activity of the prepared TiO2 nanotubes, the concentration of the first alkali solution is 3-18 mol / L, specifically 3 mol / L, 5 mol / L, 7 mol / L, 9 mol / L, 11 mol / L, 13 mol / L, 15 mol / L, 17 mol / L, etc., preferably 10 mol / L.

[0045] In some embodiments of the present application, the dispersion concentration of titanium dioxide nanoparticles in the titanium dioxide nanoparticle dispersion is 5-20 mg / mL, specifically 5 mg / mL, 6 mg / mL, 8 mg / mL, 10 mg / mL, 12 mg / mL, 14 mg / mL, 16 mg / mL, 18 mg / mL, 20 mg / mL, etc., but not limited thereto. Preferably, the dispersion concentration of titanium dioxide nanoparticles in the titanium dioxide nanoparticle dispersion is 8-15 mg / mL.

[0046] In some typical embodiments of the present application, the titanium dioxide nanoparticles and the first alkaline solution are mixed and vigorously stirred to fully mix the two. The stirring method can be mechanical stirring or magnetic stirring; preferably, the stirring speed is 500-1000rpm, preferably 750rpm; the stirring time is 1-4h, preferably 2.5h.

[0047] In some embodiments of the present application, the reaction temperature in the above step S1 is 100-210°C, and the reaction time is 24-96h, preferably 48h. In some preferred embodiments, when the first alkaline solution is a sodium hydroxide solution, the reaction temperature is 100-190, more preferably 175°C; when the first alkaline solution is a KOH solution, the reaction temperature is 120-210, preferably 200°C.

[0048] In some embodiments of the present application, in step S1, the reaction product is washed in turn with dilute acid, ethanol, and water (such as deionized water), for example, the reaction product is immersed in a dilute acid solution, and then filtered with ethanol and deionized water until the pH value of the deionized water after washing is lower than 7. The concentration of the dilute acid solution is preferably 0.05-0.2M. As an example, the acid includes but is not limited to hydrochloric acid, acetic acid, perchloric acid, etc., preferably hydrochloric acid. In some embodiments, the single immersion time of the reaction product in the above-mentioned dilute acid solution is 20min-60min, preferably 30min; the concentration of TiO2 nanotubes is 2-15mg / mL, preferably 10mg / mL; the immersion is carried out under stirring, and the stirring rate is preferably 300rpm.

[0049] In some embodiments of the present application, the temperature of the high temperature annealing treatment is 350-750°C, preferably 400-600°C, which can make the prepared modified titanium dioxide nanotubes have higher activity. Specifically, the temperature of the high temperature annealing treatment is 400°C, 450°C, 500°C, 550°C, 600°C, etc., and can also be other values ​​within the above range.

[0050] In some embodiments of the present application, the time of the high temperature annealing treatment in step S1 is 1-4 hours, specifically 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, etc., preferably 2 hours.

[0051] In some preferred embodiments of the present application, the heating rate and / or cooling rate of the high temperature annealing treatment in step S1 is 5-20°C / min, and the temperature change rates of the heating process and the cooling process may be the same or different.

[0052] In the above step S2, aluminum powder is used to modify the surface of TiO2 nanotubes through modified annealing treatment to further improve their catalytic activity. In some embodiments of the present application, the mass ratio of aluminum powder to TiO2 nanotubes is 3-15:1, which has a good surface modification effect on TiO2 nanotubes. Specifically, the mass ratio of aluminum powder to TiO2 nanotubes can be 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, etc., or other values ​​within the above range. Preferably, the mass ratio of aluminum powder to TiO2 nanotubes is 5-10:1.

[0053] In some embodiments of the present application, the above-mentioned modification annealing is performed in an inert gas atmosphere. For example, the inert gas includes but is not limited to any one or more of nitrogen, argon and helium.

[0054] In some embodiments of the present application, the temperature of the modified annealing treatment is 500-700°C, preferably 550-600°C.

[0055] In some embodiments of the present application, the time of the modified annealing treatment is 2-8 hours, preferably 4-6 hours.

[0056] In some preferred embodiments of the present application, the heating rate of the modified annealing treatment is 2-30°C / min, preferably 5-15°C / min; the cooling rate of the modified annealing treatment is 2-30°C / min, preferably 5-20°C / min.

[0057] According to another typical embodiment of the present application, a modified titanium dioxide nanotube is provided, which is prepared by any of the above-mentioned methods for preparing modified titanium dioxide nanotubes.

[0058] The modified titanium dioxide nanotubes prepared by the above method use aluminum powder to modify the surface of the nanotubes, thereby improving the catalytic activity of the titanium dioxide nanotubes, significantly improving its conductivity while ensuring the stability of the catalyst, and applying it to the catalytic electrode can make the electrode have good chemical stability, corrosion resistance and conductivity, which can significantly improve the overall performance of the catalytic electrode.

[0059] According to another typical embodiment of the present application, a method for preparing a catalytic electrode for electrolyzing water is provided, and the preparation method comprises: step A1, coating a modified TNTs dispersion containing the above-mentioned modified titanium dioxide nanotubes on a diffusion layer substrate to obtain a TNTs diffusion layer; step A2, setting a multi-component non-precious metal layer on the surface of the TNTs diffusion layer to obtain a catalytic electrode precursor; the material of the multi-component non-precious metal layer comprises metal nickel, metal aluminum and metal M, and the metal M is selected from any one or more of cobalt, iron, molybdenum and copper; step A3, under stirring conditions, immersing the catalytic electrode precursor in a second alkaline solution, and then washing and drying to obtain a catalytic electrode for electrolyzing water.

[0060] The preparation method of the electrolytic water catalytic electrode of the present application adopts the modified titanium dioxide nanotubes with high activity and stability, which are arranged on the diffusion layer substrate, and stacked on the surface of the diffusion layer to form a three-dimensional structure, which is conducive to releasing the active area of ​​the catalyst layer and accelerating the gas-liquid mass transfer process. Furthermore, the catalyst layer preparation method is simple, the components are adjustable, and the active components in the catalyst layer are selectively removed by the dealloying method to form a porous structure, further increasing the active area, and the prepared electrolytic water catalytic electrode is efficient and stable.

[0061] In some embodiments of the present application, the solvent of the modified TNTs dispersion is a water-alcohol mixed solution. Preferably, the water-alcohol mixed solution includes ethylene glycol, lower alcohol and water; preferably, the volume fraction of ethylene glycol in the water-alcohol mixed solution is less than or equal to 8%, and the volume ratio of lower alcohol to water is 1-5:1, preferably 3; preferably, the lower alcohol includes any one or more of isopropanol, propanol, ethanol and methanol.

[0062] In some embodiments of the present application, the modified TNTs dispersion includes an ionomer, and preferably, the mass ratio of the ionomer to the modified titanium dioxide nanotube is 0.2-0.5:1, specifically 0.2:1, 0.3:1, 0.4:1, 0.5:1, etc., but not limited thereto. The type of ionomer can be selected from the prior art, such as perfluorosulfonic acid polymer, polyolefin, polyaryl anion ionomer, etc., but not limited thereto.

[0063] In some preferred embodiments of the present application, the concentration of the modified titanium dioxide nanotubes in the modified TNTs dispersion is 10-35 mg / mL, specifically 10 mg / mL, 12 mg / mL, 15 mg / mL, 18 mg / mL, 20 mg / mL, 22 mg / mL, 25 mg / mL, 28 mg / mL, 30 mg / mL, 32 mg / mL, 35 mg / mL, etc., or other values ​​within the above range. Preferably, the concentration of the modified titanium dioxide nanotubes in the modified TNTs dispersion is 20 mg / mL.

[0064] In some embodiments of the present application, the above step A1 includes: dispersing the modified titanium dioxide nanotubes in a water-alcohol mixed solution, adding the ionomer, and then dispersing by ultrasonic dispersion and high-speed shear force to form a uniform solution, that is, a modified TNTs dispersion. Preferably, the rotation speed of the above high-speed shear dispersion is 5000-25000rpm, preferably 15000rpm; the time of high-speed shear dispersion is 1-5min, preferably 2min.

[0065] A person skilled in the art can apply the modified TNTs dispersion onto the diffusion layer substrate by the methods in the prior art, and the present application has no limitation thereto. For example, the modified TNTs dispersion can be applied onto the diffusion layer substrate by ultrasonic spraying or transfer printing. In some preferred embodiments of the present application, the loading amount of the modified titanium dioxide nanotubes in the TNTs diffusion layer is 1-8 mg / cm 2 , specifically 1mg / cm 2 , 2mg / cm 2 、3mg / cm 2 , 4mg / cm 2 , 5mg / cm 2 , 6mg / cm 2 , 7mg / cm 2 , 8mg / cm 2 Preferably, the loading amount of the modified titanium dioxide nanotubes in the TNTs diffusion layer is 5 mg / cm 2 .

[0066] The diffusion layer substrate can be selected from the prior art, and this application has no special requirements. As an example, the diffusion layer substrate includes but is not limited to any one or more of nickel felt, dense nickel foam, stainless steel felt, carbon paper and carbon cloth.

[0067] In some embodiments of the present application, the molar ratio of metallic nickel and metallic aluminum in the above-mentioned multi-component non-precious metal layer is 3-6:1, specifically 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, etc. Preferably, the molar ratio of metallic nickel and metallic aluminum in the multi-component non-precious metal layer is 4.

[0068] In some embodiments of the present application, the molar ratio of metal nickel to metal M in the multi-metal non-precious metal layer is 1-5:1, specifically 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, etc., or other values ​​within the above range, which can be selected according to the specific usage scenario.

[0069] In some embodiments of the present application, the method for setting the multi-component non-precious metal layer includes any one or more of vacuum evaporation, magnetron sputtering and plasma spraying. The modified titanium dioxide nanotubes are coated with the above-mentioned multi-component non-precious metal layer, and titanium dioxide serves as a substrate. The nanowires overlap during the loading process to form a three-dimensional pore structure, which forms a continuous conductive network on the one hand and allows gas-gas interaction on the other hand. The multi-component non-precious metal layer serves as a catalytic active center and needs to be in direct contact with the reactants. Therefore, it needs to be coated on the titanium dioxide surface and serve as an active substance in the electrochemical reaction to catalyze water decomposition.

[0070] In some embodiments of the present application, the metal loading of the multi-element non-noble metal layer is 0.5-20 mg / cm 2 .

[0071] By immersing the above-mentioned catalytic electrode precursor in the second alkaline solution, the Al component in the multi-component non-precious metal layer can be selectively corroded to construct a multi-component non-precious metal catalytic layer with a microscopic three-dimensional porous structure, thereby improving the catalytic activity of the multi-component non-precious metal layer.

[0072] In some embodiments of the present application, the alkali in the above-mentioned second alkaline solution includes any one or more of potassium hydroxide and sodium hydroxide. Preferably, the concentration of the second alkaline solution is 0.01-0.5 mol / L, which has a good promoting effect on the construction of the microscopic three-dimensional porous structure of the multi-element non-precious metal layer. Specifically, it can be 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L, 0.5 mol / L, etc., or it can be other values ​​within the above range, and 0.1 mol / L is more preferred.

[0073] In some embodiments of the present application, in step A3, the stirring time is 0.5-10h, specifically 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc., preferably 4h; preferably, the temperature of the second alkaline solution during the infiltration process is 25-50°C, preferably 35°C, and the infiltration effect is better.

[0074] In some embodiments of the present application, the cleaning in step A3 includes: cleaning with one or more of ethanol and acetone and deionized water for 2 to 4 times respectively.

[0075] In some embodiments of the present application, in the above step A3, drying is vacuum drying, and the temperature of vacuum drying is 60-90°C, specifically 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, etc., or other values ​​within the above range. Preferably, the temperature of vacuum drying is 80°C.

[0076] According to another typical embodiment of the present application, a water electrolysis catalytic electrode is provided, which is prepared by any of the above-mentioned methods for preparing a water electrolysis catalytic electrode.

[0077] Since the above-mentioned method for preparing the electrolytic water catalytic electrode adopts the above-mentioned modified titanium dioxide nanotubes with high activity and stability, and sets them on the diffusion layer substrate, stacking them on the surface of the diffusion layer to form a three-dimensional structure, it is beneficial to release the active area of ​​the catalyst layer and accelerate the gas-liquid mass transfer process. Furthermore, the catalyst layer preparation method is simple, the components are adjustable, and the active components in the catalyst layer are selectively removed by the dealloying method to form a porous structure, further increasing the active area, and the prepared electrolytic water catalytic electrode is efficient and stable.

[0078] According to a fifth typical embodiment of the present application, a water electrolysis hydrogen production device is provided, which contains the above-mentioned water electrolysis catalytic electrode. The water electrolysis hydrogen production device of the present application uses the above-mentioned water electrolysis catalytic electrode, which helps to achieve dynamic, efficient, stable and low-cost hydrogen production.

[0079] The beneficial effects that can be achieved by the present application will be further illustrated below in combination with embodiments and comparative examples.

[0080] Example 1

[0081] (1) Weigh 1g of nano-titanium dioxide (P25, average particle size 21nm), add it to 100mL of 10M NaOH solution, stir it magnetically (750rpm) at room temperature for 2.5h, transfer it to a 150mL high-pressure reactor, close it tightly, and put it in an oven at 175℃ for 18h. After centrifugation, the solid was transferred to 100mL of 0.1M HCl solution, soaked for 30min, and then washed with ethanol and deionized water respectively, and the pH of the water was measured, and this was repeated until the pH of the deionized water dropped to 7. The obtained solid was vacuum dried at 80℃, and then annealed at 550℃ in air atmosphere, with a heating / cooling rate of 10℃ / min to obtain TNTs.

[0082] (2) Weigh 1 g of aluminum powder and 100 mg of TNTs and place them in the upstream and downstream of a tube furnace respectively. Then, anneal them at 550 °C for 4 h in an argon atmosphere with a heating / cooling rate of 10 °C / min to obtain modified TNTs.

[0083] (3) 100 mg of modified TNTs were dispersed in 5 mL of ethylene glycol / isopropanol / water mixed solution (volume ratio 1:3:1), and 100 mg of ionomer solution (10 wt% FAA-Salut-10 solution) was added. Ultrasonic dispersion and high-speed shear force dispersion (15000 rpm, 2 min) were used to obtain a uniform solution. The modified TNTs were then coated on nickel felt by transfer printing with a loading of 5 mg / cm 2 , and obtain TNTs / nickel felt catalytic electrode substrate.

[0084] (4) Using vacuum evaporation, a nickel-aluminum-iron metal layer (4:1:3, molar ratio) was sprayed on the TNTs side of the TNTs / nickel felt catalytic electrode substrate, with a loading of 4 mg / cm 2 The sprayed electrode was placed in a 0.1M KOH solution and stirred for 4 hours at 35°C. It was then washed with ethanol and deionized water for three times, and dried in a vacuum oven at 80°C to obtain a catalytic electrode.

[0085] The surface scanning electron microscope image of the catalytic electrode prepared in this example is as follows Figure 1 shown.

[0086] The prepared catalytic electrode was used as the anode for the AEM water electrolysis hydrogen production test, and the cathode electrode used a 40wt% Pt / C@carbon paper catalytic electrode, the electrolyte was 1M KOH, and the temperature was 60℃. 2 At a current density of , the overpotential of the catalytic electrode in this example is 1.78V ( Figure 2 As shown), and the catalytic electrode prepared in this example decays within the stable test interval of 100h as shown Figure 3 As shown, the decay rate is 302 μV / h, and the decay in this range is significantly better than that of the IrO2 electrode in Comparative Example 1.

[0087] Example 2

[0088] The difference from Example 1 is that in step (2), the annealing time is 6 hours.

[0089] Example 3

[0090] The difference from Example 1 is that in step (2), the annealing time is 8 hours.

[0091] Example 4

[0092] The difference from Example 1 is that in step (2), 300 mg of aluminum powder and 100 mg of TNTs are weighed and placed upstream and downstream of the tube furnace respectively.

[0093] Example 5

[0094] The difference from Example 1 is that in step (2), 1.5 g of aluminum powder and 100 mg of TNTs are weighed and placed upstream and downstream of the tube furnace respectively.

[0095] Example 6

[0096] The difference from Example 1 is that in step (2), 100 mg of aluminum powder and 100 mg of TNTs are weighed and placed upstream and downstream of the tube furnace respectively.

[0097] Example 7

[0098] The difference from Example 1 is that in step (2), the temperature is naturally lowered after annealing.

[0099] Example 8

[0100] The difference from Example 1 is that in step (3), the loading amount of modified TNT is 1 mg / cm 2 .

[0101] Example 9

[0102] The difference from Example 1 is that in step (3), the loading amount of modified TNT is 8 mg / cm 2 .

[0103] Example 10

[0104] The difference from Example 1 is that in step (3), the loading amount of the modified TNT is 12 mg / cm 2 .

[0105] Embodiment 11

[0106] The difference from Example 1 is that in step (4), a nickel-aluminum-copper metal layer (4:1:3, molar ratio) is sprayed on the TNTs side of the TNTs / nickel felt catalytic electrode substrate, with a loading of 4 mg / cm 2 .

[0107] Example 12

[0108] The difference from Example 1 is that in step (4), a nickel-aluminum-iron metal layer (4:1:1, molar ratio) is sprayed on the TNTs side of the TNTs / nickel felt catalytic electrode substrate, with a loading of 4 mg / cm 2 .

[0109] Embodiment 13

[0110] The difference from Example 1 is that in step (4), a nickel-aluminum-iron metal layer (1:1:1, molar ratio) is sprayed on the TNTs side of the TNTs / nickel felt catalytic electrode substrate, with a loading of 4 mg / cm 2 .

[0111] Comparative Example 1

[0112] Commercial IrO2 particles ( Company) formulated at 20 mg / cm 2 The ink (solvent is a mixed solution of isopropanol / water, volume ratio 3:1) was sprayed on the surface of nickel felt by ultrasonic spraying, with a loading of 1.5 mg / cm 2 , and obtain IrO2 / nickel felt catalytic electrode.

[0113] The catalytic electrode was used as an anode in the same manner as in Example 1 for the AEM water electrolysis hydrogen production test. 2 At a current density of , the overpotential of the catalytic electrode is 1.85V ( Figure 2 As shown), and the catalytic electrode prepared in the comparative example decays within the stable test interval of 100h as shown Figure 3 As shown, the decay rate is 850μV / h.

[0114] Comparative Example 2

[0115] The difference from Example 1 is that in step (4), a nickel-iron metal layer (4:3, molar ratio) is sprayed on the TNTs side of the TNTs / nickel felt catalytic electrode substrate, with a loading of 4 mg / cm 2 .

[0116] Comparative Example 3

[0117] The difference from Example 1 is that step (2) is not performed, and the TNTs prepared in step (1) are directly used in step (3) to prepare a TNTs / nickel felt catalytic electrode substrate.

[0118] The catalytic electrodes prepared in the above examples and comparative examples were subjected to resistance tests, and the test method was as follows:

[0119] The catalytic electrodes of the above embodiments or comparative examples were used as anodes to assemble two-electrode electrolyzers, and the cathode electrodes were uniformly 40wt% Pt / C@carbon paper catalytic electrodes, and the electrolyte was 1M KOH. The assembled electrolyzers were connected to an electrochemical workstation (CHI-760D) and the internal resistance R was measured using the EIS test method. Ω and the reaction resistance R ct Test, set 0.1A / cm 2 The external current density is 10mHz-100Hz.

[0120] The results of the resistance test are shown in Table 1 below.

[0121] Table 1

[0122] <![CDATA[Internal resistance R Ω / mΩ]]> <![CDATA[Reaction resistance R ct / mΩ]]> Example 1 11 20 Example 2 11 21 Example 3 12 25 Example 4 15 28 Example 5 15 36 Example 6 18 42 Example 7 17 37 Example 8 12 24 Example 9 13 23 Example 10 15 34 Embodiment 11 12 22 Example 12 13 26 Embodiment 13 18 40 Comparative Example 1 19 32 Comparative Example 2 30 57 Comparative Example 3 41 126

[0123] From the above description, it can be seen that the above-mentioned embodiments of the present invention achieve the following technical effects: titanium dioxide nanotubes are prepared by a specific method, and the surface of the nanotubes is modified by aluminum powder, thereby improving the catalytic activity of the titanium dioxide nanotubes, while ensuring the stability of the material and significantly improving its electrical conductivity. When applied to catalytic electrodes, the electrodes can have good chemical stability, corrosion resistance and conductivity, and significantly improve the overall performance of the catalytic electrode.

[0124] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing modified titanium dioxide nanotubes, characterized in that: include: Step S1, mixing titanium dioxide nanoparticles and a first alkaline solution to obtain a titanium dioxide nanoparticle dispersion, heating the titanium dioxide nanoparticle dispersion to react, washing the reaction product with acid, ethanol and water, and then annealing at high temperature to obtain TiO2 nanotubes; Step S2, placing aluminum powder and the TiO2 nanotubes in the gas upstream and downstream of a tube furnace respectively, and performing modification annealing treatment to obtain the modified titanium dioxide nanotubes.

2. The method for preparing modified titanium dioxide nanotubes according to claim 1, characterized in that: The temperature of the modified annealing treatment is 500-700°C, preferably 550-600°C; The modified annealing treatment time is 2-8h, preferably 4-6h; The heating rate of the modified annealing treatment is 2-30°C / min, preferably 5-15°C / min; The cooling rate of the modified annealing treatment is 2-30°C / min, preferably 5-20°C / min; The mass ratio of the aluminum powder to the TiO2 nanotubes is 3-15:1, preferably 5-10:1; The modification annealing is performed in an inert gas atmosphere, wherein the inert gas includes any one or more of nitrogen, argon and helium.

3. The method for preparing modified titanium dioxide nanotubes according to claim 1, characterized in that: The concentration of the first alkali solution is 3-18 mol / L, and the first alkali solution is an aqueous solution of any one or more of potassium hydroxide and sodium hydroxide; The dispersion concentration of the titanium dioxide nanoparticles in the titanium dioxide nanoparticle dispersion is 5-20 mg / mL; The reaction temperature in step S1 is 100-210°C and the reaction time is 24-96h; The temperature of the high temperature annealing treatment in step S1 is 350-750° C., preferably 400-600° C.; The high temperature annealing treatment time in step S1 is 1-4 hours; The heating rate and / or cooling rate of the high temperature annealing treatment in step S1 is 5-20° C. / min.

4. A modified titanium dioxide nanotube, characterized in that: The modified titanium dioxide nanotube is prepared by the preparation method of any one of claims 1 to 3.

5. A method for preparing a catalytic electrode for electrolyzing water, characterized in that: include: Step A1, coating a modified TNTs dispersion containing the modified titanium dioxide nanotubes according to claim 4 on a diffusion layer substrate to obtain a TNTs diffusion layer; Step A2, disposing a multi-component non-precious metal layer on the surface of the TNTs diffusion layer to obtain a catalytic electrode precursor; the material of the multi-component non-precious metal layer includes metal nickel, metal aluminum and metal M, and the metal M is selected from any one or more of cobalt, iron, molybdenum and copper; Step A3, under stirring conditions, immersing the catalytic electrode precursor in a second alkaline solution, and then washing and drying to obtain the water electrolysis catalytic electrode.

6. The method for preparing a water electrolysis catalytic electrode according to claim 5, characterized in that: The solvent of the modified TNTs dispersion is a water-alcohol mixed solution. Preferably, the water-alcohol mixed solution includes ethylene glycol, lower alcohol and water. Preferably, The volume fraction of ethylene glycol in the water-alcohol mixed solution is less than or equal to 8%, and the volume ratio of the lower alcohol to water is 1-5:1; preferably, the lower alcohol includes any one or more of isopropanol, propanol, ethanol and methanol; The modified TNTs dispersion includes an ionomer, and the mass ratio of the ionomer to the modified titanium dioxide nanotube is 0.5-0.2:1; The concentration of the modified titanium dioxide nanotubes in the modified TNTs dispersion is 10-35 mg / mL; The diffusion layer substrate is any one or more of nickel felt, dense nickel foam, stainless steel felt, carbon paper and carbon cloth; The loading amount of the modified titanium dioxide nanotubes in the TNTs diffusion layer is 1-8 mg / cm 2 .

7. The method for preparing a water electrolysis catalytic electrode according to claim 5, characterized in that: The molar ratio of the metal nickel to the metal aluminum in the multi-element non-precious metal layer is 3-6:1, and the molar ratio of the metal nickel to the metal M is 1-5:1; The method for setting the multi-element non-precious metal layer includes any one or more of vacuum evaporation, magnetron sputtering and plasma spraying; The metal loading of the multi-element non-noble metal layer is 0.5-20 mg / cm 2 .

8. The method for preparing a water electrolysis catalytic electrode according to claim 5, characterized in that: The alkali in the second alkali solution includes any one or more of potassium hydroxide and sodium hydroxide, and the concentration of the second alkali solution is 0.01-0.5 mol / L; In step A3, the stirring time is 0.5-10h, preferably 4h; In the step A3, the drying is vacuum drying, and the temperature of the vacuum drying is 60-90°C.

9. A catalytic electrode for electrolyzing water, characterized in that: The catalytic electrode for electrolysis of water is prepared by the method for preparing the catalytic electrode for electrolysis of water according to any one of claims 5 to 8.

10. A hydrogen production device by electrolysis of water, characterized in that: A water electrolysis catalytic electrode comprising the water electrolysis catalytic electrode according to claim 9.